PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER) DAN TOTAL ASSET TURNOVER (TATO) TERDAHAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Siska Audina Bambang Siswanto (JURNAL ILMIAH EDUNOMIKA, 2021)
This study was conducted to examine the effect of Return on Equity, Debt to Equity Ratio and Total Asset Turnover on stock returns in manufacturing companies listed on the IDX for the 2014-2018 period. The population in this study were 143 manufacturing companies for the 2014-2018 period. The sampling method used was purposive sampling technique and the selected sample met the criteria of 40 companies so that the data used was 200. This study used secondary data and the analysis method used was the classical assumption test, multiple linear regression, t test, f test and coefficient of determination. . Based on the results of data analysis, it can be concluded that the ROE variable has a positive and significant effect on stock returns, the DER variable has a positive and insignificant effect on stock returns, the TATO variable has a positive and insignificant effect on stock returns. There is a significant influence of the ROE, DER and TATO variables simultaneously on Stock Return.